The compact genome of the sponge Oopsacas minuta (Hexactinellida) is lacking key metazoan core genes - Santini, S.; Schenkelaars, Q.; Jourda, C.; Duchesne, M.; Belahbib, H.; Rocher, C.; Selva, M.; Riesgo, A.; Vervoort, M.; Leys, S. P.; Kodjabachian, L.; Le Bivic, A.; et al. (BMC Biology, 2023)
Explaining the emergence of the hallmarks of bilaterians is a central focus of evolutionary developmental biology—evodevo—and evolutionary genomics. For this purpose, we must both expand and also refine our knowledge of non‑bilaterian genomes, especially by studying early branching animals, in particular those in the metazoan phylum Porifera. We present a comprehensive analysis of the first whole genome of a glass sponge, Oopsacas minuta, a member of the Hexactinellida. Studying this class of sponge is evolutionary relevant because it differs from the three other Porifera classes in terms of development, tissue organization, ecology, and physiology. Although O. minuta does not exhibit drastic body simplifications, its genome is among the smallest of animal genomes sequenced so far, and surprisingly lacks several metazoan core genes (including Wnt and several key transcription factors). Our study also provides the complete genome of a symbiotic Archaea dominating the associated microbial community: a new Thaumarchaeota species. The genome of the glass sponge O. minuta differs from all other available sponge genomes by its compactness and smaller number of encoded proteins. The unexpected loss of numerous genes previously considered ancestral and pivotal for metazoan morphogenetic processes most likely reflects the peculiar syncytial tissue organization in this group. Our work further documents the importance of convergence during animal evolution, with multiple convergent evolution of septate‑like junctions, electrical‑signaling and multiciliated cells in metazoans.